Diseño de un Manual de Control Interno para el Área Administrativa, Contable y Tributaria en la Fundación Centro Cultural ASLOCH, Período 2021 - Montaño Yauri, Nixon Paul (2023)
The Curricular Integration work called "DESIGN OF AN INTERNAL CONTROL MANUAL FOR THE ADMINISTRATIVE, ACCOUNTING AND TAX AREA IN THE ASLOCH CULTURAL CENTER FOUNDATION, PERIOD 2021" was developed to design procedures and policies for internal control that allows users to visualize and understand the administrative operations and procedures, and their control in a more optimal and efficient way in the Foundation and PCEI Amazonas Private High-school, being this a Social Service Project executed by the institution. For the elaboration of this work, it was required the use of bibliographic material and a field study with specific methods to obtain the necessary data to make the institutional diagnosis. An evaluation of the elements of the institution's context was carried out, the president and the accountant were interviewed to identify internal deficiencies. In this manual, policies, procedures and flowcharts focused on the administrative process were created, which explain each of the steps to follow to improve the internal and organizational control, such as the acceptance of new members, training, selection and hiring of personnel, among others. Regarding the accounting area, policies and procedures were designed with their respective flow charts, which focus on establishing internal controls for the accounts that most contribute to and affect the foundation's accounting process. For the tax area, policies were established to control fulfillment of tax obligations appropriate, optimal and transparent manner, therefore, the information presented is truthful, useful and timely so that the organization's directors can make the best decision to achieve their goals and objectives. At the end, the respective conclusions and recommendations were formulated, which can be considered within the ASLOCH Cultural Center Foundation and its Social Services Projects.